Pengaruh Pengetahuan Wajib Pajak, Sanksi Denda, Kualitas Pelayanan Dan Sosialisasi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kota Semarang - Fhadha Dhea Ananda Putri; Maryono Maryono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of taxpayer knowledge, fines, service quality, and tax socialization on motor vehicle taxpayer compliance in Semarang City. This research uses a survey method by distributing questionnaires to motorized vehicle owners who are registered as taxpayers in Semarang City. This research consisted of 100 respondents using the Accidental Sampling technique and analyzed using multiple linear regression analysis. The research results show that taxpayer knowledge, fines, service quality, and tax socialization have a positive and significant effect on motor vehicle taxpayer compliance in Semarang City. Keywords: Taxpayer Compliance, Tax Knowledge, Fines, Service Quality, and Tax Socialization.